2021
DOI: 10.1029/2021gl092987
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Source‐Specific Black Carbon Aerosol and the Induced Radiative Effects Due to the COVID‐19 Lockdown

Abstract: The impacts of anthropogenic emissions on the reduction of source‐specific equivalent black carbon (eBC) aerosols and their direct radiative effects (DREs) were investigated during the lockdown of the coronavirus outbreak in a megacity of China in 2020. Five eBC sources were identified using a hybrid environmental receptor model. Results showed that biomass burning, traffic‐related emissions, and coal combustion were the dominant contributors to eBC. The generalized additive model indicated that the reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 92 publications
(134 reference statements)
1
11
0
Order By: Relevance
“…Vehicular emissions is a major source of OC and NO 2 (Bi et al., 2019; B. S. Liu et al., 2022; H. K. Liu et al., 2022; Zotter et al., 2017). The percentage of light absorption showed an increasing trend from 370 to 880 nm (Figure 3), which is consistent with previous reports (H. K. Liu et al., 2021, 2022; Yuan et al., 2022). The estimated AAE for VE was 1.08 (Figure S3 in Supporting Information ), which fitted the range of VE characteristic values (0.8–1.2) (Blanco‐Donado et al., 2022; Briggs & Long, 2016).…”
Section: Resultssupporting
confidence: 92%
“…Vehicular emissions is a major source of OC and NO 2 (Bi et al., 2019; B. S. Liu et al., 2022; H. K. Liu et al., 2022; Zotter et al., 2017). The percentage of light absorption showed an increasing trend from 370 to 880 nm (Figure 3), which is consistent with previous reports (H. K. Liu et al., 2021, 2022; Yuan et al., 2022). The estimated AAE for VE was 1.08 (Figure S3 in Supporting Information ), which fitted the range of VE characteristic values (0.8–1.2) (Blanco‐Donado et al., 2022; Briggs & Long, 2016).…”
Section: Resultssupporting
confidence: 92%
“…The last factor was characterized by high loadings of As (43%) and Pb (30%). According to previous studies, high loadings of As and Pb are found in coal combustion (Tan et al, 2017;Liu et al, 2021). Thus, this factor was recognized as resulting from coal combustion which contributed 35% of EC.…”
Section: Source Apportionment Of Ec In Different Seasonsmentioning
confidence: 92%
“…Five sources of EC were identified by PMF during wintertime shown in Figure 4. The first factor was characterized by high loadings of Ca 2+ (86%), Si (48%), and Ti (43%), widely recognized as associated with mineral dust (Tao et al, 2017;Liu et al, 2021). This factor barely contributed to EC during winter.…”
Section: Source Apportionment Of Ec In Different Seasonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lockdown of Wuhan and surrounding cities provided an unintended experimental condition under which to investigate the influences of emissions from different sectors, e.g., traffic and industry, by completely or partially removed emissions. A few studies showed that the air pollution level declined during the lockdown period [25][26][27][28][29][30]. The air pollution reduction can be visualized from measurements by the China National Environmental Monitoring Network [31].…”
Section: Introductionmentioning
confidence: 99%